A novel selective fluorescent chemosensor for Fe3+ ions based on phthalonitrile dimer: synthesis, analysis, and theoretical studies - Al-Raqa, Shaya; Omeroglu, Ipek; Erbahar, Dogan; Durmuş, Mahmut (Tubitak Scientific & Technological Research Council Turkey, 2020)
Phenyl-4,4-di(3,6-dibutoxyphthalonitrile) (3) was synthesized by the reaction of 1,4-phenylenebisboronic acid (1) and 4-bromo-3,6-dibutoxyphthalonitrile (2), using Suzuki cross-coupling reaction. The newly synthesized compound (3) was characterized by FT-IR, MALDI-MS, ESI-MS, H-1-NMR, C-13-NMR, and C-13-DEPT-135-NMR. The fluorescence property of phenyl-4,4-di(3,6-dibutoxyphthalonitrile) (3) towards various metal ions was investigated by fluorescence spectroscopy, and it was observed thatthe compound (3) displayed a significantly 'turn-off' response to Fe3+, which was referred to 1:2 complex formation between ligand (3) and Fe3+. The compound was also studied via density functional theory calculations revealing the interaction mechanism of the molecule with Fe3+ ions.
A novel selective fluorescent chemosensor for $Fe^{3+}$ ions based on phthalonitrile dimer: synthesis, analysis, and theoretical studies
Keywords: Phthalonitrile; Suzuki cross-coupling; fluorescence; chemosensor; Fe3+ ion